Antibody levels to variant and conserved Plasmodium falciparum antigens predict reduction in parasite burden in Malian children - Damena, Delesa; Dang, Lauren; Barry, Amadou; Renn, Jonathan P.; Gaoussou, Santara; Mahamar, Almahamoudou; Attaher, Oumar; Issiaka, Djibrilla; Morrison, Robert D.; Misal, Santosh A.; Dicko, Alassane; Duffy, Patrick E.; et al. (Frontiers in Immunology, 2026)
BackgroundProteins expressed on the surface of Plasmodium falciparum-infected erythrocytes (IEs) are targets of immunity. Previous studies described that IEs from young children are more readily recognized than IEs from older children. Here, we aimed to identify targets of naturally acquired antibodies that may play a role in protection from malaria.MethodsWe applied immunoprecipitation followed by mass spectrometry (IP-MS) using plasma samples from susceptible and semi-immune children. We then investigated whether 1) antibody levels to membrane-associated proteins identified by IP-MS, or 2) PfEMP1s expressed in IEs of young children predict reduction in malaria disease.ResultsSignificant reduction in risk of high parasite density infection was predicted by high antibody levels to DBLγ11 [OR (95%CI): 0.74 (0.63-0.86)] and DBLζ5 [0.80 (0.69-0.93)], as well as two Plasmodium helical interspersed subtelomeric proteins: PF3D7_0201600 [0.81 (0.70-0.94)] and PF3D7_0532300 [0.79 (0.68-0.92)]. Opsonic phagocytosis of DBLγ11 and DBLζ5 coated beads was significantly higher in plasma samples with antibody levels at the top tertile compared to those from lower tertiles (p<0.0001). The Relative phagocytosis index positively correlated with antibody levels, r2 = 0.61 (p<0.001) and r2 = 0.49 (p<0.001) for DBLζ5 and DBLγ11, respectively.ConclusionsThe study showed that high antibody levels against four proteins significantly reduced the odds of high parasite burden in future infections. Our functional study suggests that opsonic phagocytosis may mediate reduction in parasite density by antibodies to DBLγ11 and DBLζ5.